Lymphoma of unknown origin located in paravertebral muscles: an unusual cause of low back pain in children - Diniz, Ricardo Edesio Amorim Santos; Goldenberg, José; Carvalho, José Carlos Medina de; Gomes, Carlos Eduardo Sales; Goldenberg, Evelin Diana; Sementille, Angelo (São Paulo Medical Journal, 1995)
The authors report a case of an adolescent with a poorly differentiated lymphoma of unknown origin located at paravertebral muscles, whose presenty symptom was low back pain.